The theme of the Pentateuch - Clines, David, J.A. (Sheffield, UK Sheffield Academic Press, 1997)
Includes bibliographical references and indexes.
First published 1978, JSOT Pr
Early Emmaus student and lecturer.
Keywords: Bible. O.T. -- themes